2011
DOI: 10.1007/s00134-011-2234-0
|View full text |Cite
|
Sign up to set email alerts
|

WNT/β-catenin signaling is modulated by mechanical ventilation in an experimental model of acute lung injury

Abstract: Our findings demonstrate that the WNT/β-catenin signaling pathway is modulated early during sepsis and ventilator-induced lung injury, suggesting that activation of this pathway could play an important role in both lung injury progression and repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 33 publications
5
49
0
Order By: Relevance
“…We have previously reported that ␤-catenin signaling is activated in the lung epithelium in response to neutrophil transmigration and plays a critical role in epithelial repair after inflammatory injury (72), and other reports corroborate this finding (17,64,75). In canonical Wnt/␤-catenin signaling, ␤-catenin translocates to the nucleus and binds to the T cell factor (TCF)/lymphoid enhancer factor (LEF) family of transcription factors, enhancing expression of specific target genes, many of which are involved in cell proliferation; hence, ␤-catenin signaling has been implicated in development, tumorigenesis, and tissue repair (12,52).…”
supporting
confidence: 61%
See 1 more Smart Citation
“…We have previously reported that ␤-catenin signaling is activated in the lung epithelium in response to neutrophil transmigration and plays a critical role in epithelial repair after inflammatory injury (72), and other reports corroborate this finding (17,64,75). In canonical Wnt/␤-catenin signaling, ␤-catenin translocates to the nucleus and binds to the T cell factor (TCF)/lymphoid enhancer factor (LEF) family of transcription factors, enhancing expression of specific target genes, many of which are involved in cell proliferation; hence, ␤-catenin signaling has been implicated in development, tumorigenesis, and tissue repair (12,52).…”
supporting
confidence: 61%
“…Indeed, ␤-catenin and the CCN proteins are known to be involved in tissue repair after injury in various organs, including the lung, where they have been implicated in limiting injury and/or promoting repair in acute lung injury (2,7,14,17,30,31,64) and COPD (37,75). However, the effects of CCN proteins may be context dependent because WISP1 may enhance ventilator-induced lung injury via augmentation of macrophage proinflammatory responses (42).…”
Section: Discussionmentioning
confidence: 99%
“…Wnt5A has also been shown to be significantly upregulated in UIP/IPF and to promote proliferation and prevent apoptosis in fibroblasts from patients with UIP/IPF (Vuga et al 2009). Its fibrogenic qualities are also demonstrated by its up-regulation in sarcoidosis (Levänen et al 2011), ventilator-induced pulmonary fibrosis (Villar, et al 2011), and liver fibrosis (Rashid et al 2012). Recent studies have demonstrated an increased expression of Wnt5A in smooth muscle cells in asthma and its necessity for TGF-β-induced production of ECM (Kumawat et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of literature investigating whether CLP increases susceptibility to VILI. Many studies using rodent lungs "primed" by CLP do not use a control group, which would allow differentiation of the effects of sepsis from the effects of high V T (35,36).…”
Section: Discussionmentioning
confidence: 99%